2012
DOI: 10.1371/journal.pone.0039061
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Resting State Functional Connectivity of the Subthalamic Nucleus: Identification of Motor STN Parts and the Hyperdirect Pathway

Abstract: Deep brain stimulation (DBS) for Parkinson’s disease often alleviates the motor symptoms, but causes cognitive and emotional side effects in a substantial number of cases. Identification of the motor part of the subthalamic nucleus (STN) as part of the presurgical workup could minimize these adverse effects. In this study, we assessed the STN’s connectivity to motor, associative, and limbic brain areas, based on structural and functional connectivity analysis of volunteer data. For the structural connectivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 75 publications
7
96
0
Order By: Relevance
“…The averaged locations of these zones in healthy subjects correspond with our findings in individual patients. This arrangement was also observed in another 3 T functional and structural connectivity study based on averaged data of healthy subjects, but could not be demonstrated consistently in all individual subjects (Brunenberg et al, 2012). Finally the STN’s connectivity was previously investigated in PD patients as well, although this only concerned its motor area and analyses were only performed in a qualitative manner (Avecillas-Chasin et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…The averaged locations of these zones in healthy subjects correspond with our findings in individual patients. This arrangement was also observed in another 3 T functional and structural connectivity study based on averaged data of healthy subjects, but could not be demonstrated consistently in all individual subjects (Brunenberg et al, 2012). Finally the STN’s connectivity was previously investigated in PD patients as well, although this only concerned its motor area and analyses were only performed in a qualitative manner (Avecillas-Chasin et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…A once widely held assumption is that the STN is divided into three functional zones within the STN: limbic, associative, and sensorimotor regions, residing in the anteromedial, middle, and dorsolateral portions, respectively, of the STN (58,68,69). This concept has been challenged by several recent electrophysiologic, neuroanatomic, and neuroimaging studies showing incomplete separation of the subthalamic territories (56,63,70,71). Therefore, it is not surprising that the affective neurons were found in the sensorimotor regions, suggesting that motor and nonmotor regions overlap in the STN.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 shows white matter pathways that have been imaged only recently for the first time in vivo in humans using DTI. These include the nigrostriatal, nigrothalamic, pallidothalamic, subthalamopallidal, striatopallidal (Lenglet et al, 2012), and hyperdirect pathways (Brunenberg et al, 2012) in normal subjects; and cerebellar subthalamopontocerebellar and dentatothalamic tracts in PD patients (Sweet et al, 2014). …”
Section: Neuroimaging Of Pdmentioning
confidence: 99%
“…Bold: neuroimaging of structural connections in humans in vivo by Brunenberg et al (2012; hyperdirect pathway), Sweet et al (2014; subthalamopontocerebellar and dentothalamic tracts), and Lenglet et al (2012; other bold pathways).…”
Section: Figmentioning
confidence: 99%